Efektivitas Penggunaan Alat Praktikum Osilator Pegas Untuk Meningkatkan Hasil Belajar Kognitif Siswa - Kristina Uskenat; Selestina Kostaria Jua; Tutik Yuliatun (Musamus Journal of Science Education, 2022)
This study aims to describe the effectiveness of the use of a spring oscillator practicum on students of SMA Negeri 1 Indramayu and SMA Negeri 2 Indramayu. The method used is the ADDIE model R & D method using a one group pretest-posttest design. The results showed that the calculation of the n-gain score of 0.688 and 0.680 obtained the interpretation of increasing student learning outcomes in the medium category. Meanwhile, students' responses to the spring oscillator practicum tool obtained an average score of 82.3% from the three aspects with the interpretation of the score "good". From the research data, it can be concluded that the use of a spring oscillator is effective in high school physics learning